Non-timber forest products in West Bengal: knowledge, livelihoods and policy - Ghosal, Somnath (2010)
The theme of this research is the conservation of open dry-deciduous forest areas of West Bengal, India, through the socio-economic progress of forest dwellers. The use of Non-Timber Forest Products (NTFPs) is manifold in the livelihood of this area. Systematic and sustainable harvesting of NTFPs could improve the standard of living of forest dwellers and play an important role in the conservation of forest ecosystems.